Faktor – Faktor Yang Mempengaruhi Ibu Hamil Dalam Pemeriksaan HIV/AIDS Di Puskesmas Maga Kabupaten Madina Tahun 2022 - Nurmala Sari Dewi; Basaria Manurung (Pusat Riset dan Inovasi Nasional, 2023)
Human immunodeficiency virus (HIV) is an infectious disease caused by infection with the human immunodeficiency virus that attacks the immune system. The infection causes a decrease in the defense of the immune system which then makes the body more vulnerable to various other diseases. This study aims to determine the factors that influence pregnant women in examining HIV/AIDS at the Maga Health Center in 2022. This type of research is an analytic survey with a cross-sectional approach. The population is all pregnant women who are at the Maga Health Center in 2022, a total of 50 pregnant women. The number of samples used was 50 people obtained by using total sampling technique. Data analysis technique using chi square. The results obtained in this study were from 50 respondents, there was a relationship between the variable knowledge of pregnant women and VCT participation with a p value = 0.025, there was a relationship between the attitudes of pregnant women and VCT participation with a p value = 0.015. Conclusion: there is a relationship between the variable knowledge of pregnant women and VCT participation, there is a relationship between the variable attitudes of pregnant women and VCT participation. It is suggested to the puskesmas to increase the knowledge of pregnant women to increase counseling related to VCT examinations.